Interventions to prevent or reduce the level of frailty in community-dwelling older adults: a protocol for a scoping review of the literature and international policies. Issue 3 (2nd March 2016) - Puts, Martine T E; Toubasi, Samar; Atkinson, Esther; Ayala, Ana Patricia; Andrew, Melissa; Ashe, Maureen C; Bergman, Howard; Ploeg, Jenny; McGilton, Katherine S
Abstract : Introduction: With ageing comes increased vulnerability such that older adults' ability to recover from acute illnesses, fall-related injuries and other stresses related to the physical ageing processes declines. This increased vulnerability, also known as frailty, is common in older adults and associated with increased healthcare service use and adverse health outcomes. Currently, there is no overview of available interventions to prevent or reduce the level of frailty (as defined by study's authors) which will help healthcare providers in community settings caring for older adults. We will address this gap by reviewing interventions and international polices that are designed to prevent or reduce the level of frailty in community-dwelling older adults. Methods and analysis: We will conduct a scoping review using the updated guidelines of Arksey and O'Malley to systematically search the peer-reviewed journal articles to identify interventions that aimed to prevent or reduce the level of frailty. We will search grey literature for international policies. The 6-stage scoping review model involves: (1) identifying the research question; (2) identifying relevant studies; (3) selecting studies; (4) charting the data; (5) collating, summarising and reporting the results and (6) consulting with key stakeholders. Ethics and dissemination: Our scoping review will use robust methodology to search for available interventions focused on preventing or reducing the level of frailty in community-dwelling older adults. We will consult with stakeholders to find out whether they find the frailty interventions/policies useful and to identify the barriers and facilitators to their implementation in Canada. We will disseminate our findings to relevant stakeholders at local, national and international levels by presenting at relevant meetings and publishing the findings. Our review will identify gaps in research and provide healthcare providers and policymakers with an overview of interventions that can be implemented to prevent or postpone frailty.